2013
DOI: 10.1021/es3049114
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Inhaled 3,3′-Dichlorobiphenyl and the Formation of the 4-Hydroxylated Metabolite

Abstract: The recent discovery of 3,3′-dichlorobiphenyl (CB11) as a byproduct of pigment manufacturing underscores the urgency to investigate its biological fate. The high level and ubiquity of atmospheric CB11 indicates that inhalation is the major route of exposure. However, few data on its uptake and elimination exist. A time course study was performed exposing male Sprague-Dawley rats to CB11 via nose-only inhalation with necropsy at 0, 4 and 8 h post exposure. An analytical method for CB11 and mono-hydroxylated met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 45 publications
4
52
0
Order By: Relevance
“…Analytical artifacts cannot explain the low levels of these congeners because our laboratory was successful in measuring them in the Aroclors (Marek et al, 2013a) and our mono-tri homolog PCB standards showed good recoveries in our serum samples. Our animal inhalation studies have shown that these lower-chlorinated OH-PCBs are rapidly biotransformed to phase II metabolites (e.g., sulfated and glucuronidated conjugates) (Hu et al, 2013; Hu et al, 2014; Dhakal et al, 2012; Grimm et al, 2015). This suggests that other PCB metabolites may be better biomarkers for lower-chlorinated metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical artifacts cannot explain the low levels of these congeners because our laboratory was successful in measuring them in the Aroclors (Marek et al, 2013a) and our mono-tri homolog PCB standards showed good recoveries in our serum samples. Our animal inhalation studies have shown that these lower-chlorinated OH-PCBs are rapidly biotransformed to phase II metabolites (e.g., sulfated and glucuronidated conjugates) (Hu et al, 2013; Hu et al, 2014; Dhakal et al, 2012; Grimm et al, 2015). This suggests that other PCB metabolites may be better biomarkers for lower-chlorinated metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also found OH-PCBs in sediments (Marek et al, 2013a) and human waste has been proposed as a source to surface waters (Ueno et al, 2007). Our group previously demonstrated that OH-PCBs are important metabolic products of PCB 11 and PCB 3 in rats and are excreted in urine and feces (Hu et al, 2013; 2014; Dhakal et al, 2014). OH-PCBs were present in the original Aroclors and this may have contributed OH-PCBs to sediments (Marek et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…45 Our laboratory was the first to report PCB 11 in human serum 13, 14 and we know no other reports of PCB 11 in humans. Our group has performed the only inhalation studies of PCB 11 46 and 14 C-labelled PCB 11. 47 Our current study found that PCB 11 concentration was not age-dependent which suggests this compound does not biomagnify and its presence may be due to recent exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why children’s sera did not demonstrate a significant correlation between PCBs and OH-PCBs, however, our prior work has shown that their congener profiles are skewed toward the lower-chlorinated PCBs compared to their mothers 33, 41 and these congeners are more rapidly >metabolized. 42 In addition, the limited availability of lower-chlorinated OH-PCB standards may have compromised the estimation of total OH-PCBs.…”
Section: Discussionmentioning
confidence: 99%